Advancing Environmental Ethics Through the African World-View - Ugwuanyi, Lawrence Ogbo (Mediterranean Journal of Social Sciences, 2011)
In this paper I intend to locate a fresh basis on which alternative theories of environment from the African worldviewcould be explored; one which will improve the literature on environment as well as diversify the basis for producing positions thatcould mediate in the tensions that define environmental problems and principles. I shall do this by (i) articulating the moralprinciples of the world and how it suggests an idea of environmental ethics;(ii)locating the philosophy that interprets traditionalreligious practices and the environmental principles that could be derived there-in. I shall demonstrate how (iii)these strands ofideas provide positions that strongly suggest alternative but valuable basis for environmental ethics anchored on Africanworldview and its theoretical and practical potentials for promoting the growth of environment.